KAJIAN STABILISASI TANAH LEMPUNG MENGGUNAKAN PASIR DAN KAPUR SEBAGAI SUBGRADE PADA RUAS JALAN ENAROTALI MADI KABUPATEN PANIAI PROVINSI PAPUA - , Derek Yeimo, Ir. Agus Darmawan Adi, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Enarotali â Madi highway at Paniai regency has severe road damage. The Office of Highway Construction (Bina Marga) often conducted improvements to the construction of the road pavement layers. Nevertheless, the effort has not been able to solve the road damage. Road damage is assumed caused by the subgrades that are not capable of supporting the weight of vehicles passing on it. The subgrade of Enarotali â Madi road has fine grade soil tomoderate type with high plasticity cohesive clay which expand and shrink, undulating, cracked, fractured very large when there is a change in water content. The purpose of the clay stabilization is to improve native soil physical and mechanical capabilities to the CBR value and unconfined soil compressive strength value, to determine the best composition of sand, limestone and clay as a stabilizing agent, increase the load carrying capacity of clay stabilized with sand and lime as a stabilization material for subgrade on the maintenance and construction of roads. The research location was on Enarotali - Madi highway at Paniai Regency of Papua Province. Stabilization agent using lime and sand through the 7-days curing process to obtain result of CBR value and unconfined soil compressive strength value. According to the classification of USCS, the anorganic silt or clay is not included into CL and ML. Meanwhile, according to the classification of AASHTO, it is included in the A-7-6 group, a moderate-to- poor clay soil, and then it is not good to be used as the road foundation. The soil density with the addition of sand and limestone can reduce the maximum dry density (MDD) value, and may increase optimum moisture content (OMC). The maximum CBR value occurs in 10% sand and 8 % limestone content with a 7-days curing period. Test results of unconfined soil compressivestrength with a 7-days curing period of rupture has increase from 4.01 kg/cm2 to 10.17 kg/cm2 at 10% sand and 8 % limestone content.